Modeling and design considerations of a photovoltaic energy source feeding a synchronous reluctance motor suitable for pumping systems - M. Nabil; S.M. Allam; E.M. Rashad (Ain Shams Engineering Journal, 2012)
This paper presents the performance analysis of a photovoltaic (PV) energy source driving a synchronous reluctance (SyncRel) motor. The design considerations of the PV array, suitable for driving a centrifugal pump, are studied. Three design approaches are proposed at an average insolation of 0.5 kW/m2. These approaches depend upon determining the system operating point firstly and then maintaining this point on the PV generator characteristics. The first approach takes motor starting current into account as an additional design criterion. The second one is based on achieving the maximum power at the system operating point. The third approach considers maintaining voltage regulation of the PV generator at a pre-specified suitable value. A sample of the simulation results is introduced using the SyncRel motor measured parameters and the estimated parameters of the PV array. It has been found that the minimum number of cells can be achieved using the second approach.